Neurological Manifestations and Its Outcome Due to Covid-19 Disease: An Observational Study - Khalil Ahmed, Muhammad Khan Malik, Nasar Iqbal Ranjha, Azeem (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Corona virus has hit the world by the end of year 2019. Within few months it became pandemic and named as COVID-19 (SARS COV 2). Initially it was known as a disease of respiratory tract but with the advance study of clinical symptoms it has shown neurological manifestations, coagulopathies, diabetes mellitus and hypertension. The pathophysiology of disease showed that corona virus proteins bind to ACE receptors and effect multiple organ systems of body. The disease outcome is poor among those who develop such complications. The objective of this study was to determine the association of neurological manifestations with COVID 19 and to find out the health outcome of admitted patients. Methods: A cross-sectional study was conducted on COVID 19 patients through convenient sampling. Patients were admitted to DHQ Hospital, Sargodha with clinical symptoms of disease and with neurological manifestations. Their comorbid factors were also identified along with laboratory investigations (CT- brain, D-dimers. Serum sugar level and base line investigations). Analysis was done on SPSS 20 and association was determined between neurological manifestations and COVID 19 disease by chi- square test of independence with p<0.05 taken as level of significance. Results: Among 276 hospitalized patients male and female were of equal ratio with mean age of 59.22 (SD= 14.3). The death was more among 56-70 years (n=165) of patients with neurological manifestations and 100% in patients with age > 70 years with neurological manifestations. The outcome of disease is not significantly associated with age of patients (p=0.101). CT-scan findings showed 195(92.85%) patients’ outcome was poor with thromboembolic phenomenon. Neurological manifestations of COVID 19 disease were also significantly associated with disease outcome (p=0.000). Only 30 (11.11%) patients with neurological manifestations recovered from disease and were discharged. The severity of disease was also significantly associated with neurological manifestations due to COVID 19 (p=0.000). Conclusion: The neurological manifestations are associated with COVID 19 disease and its outcome is poor due to its neurological complications. The central nervous system involvement might be the result of invasion of virus. The COVID 19 disease is not only involving the respiratory system but it has its effects on multiple organs. The outcome of disease can be managed with early diagnosis and management of neurological manifestations.